The Influence of Work Flexibility and Job Satisfaction on Employee Performance - Rahayu, Serli Agustin (Lentera Ilmu Nusantara, 2024)
This research aims to determine the effect of work flexibility and job satisfaction on employee performance in Karawang. This research uses the method of distributing questionnaires directly to respondents who are employees in the city of Karawang. This type of research is quantitative. The data processed is primary data obtained from the results of distributing questionnaires using simple random sampling techniques. From distributing the questionnaire, a sample of 75 respondents was obtained. Data analysis was carried out using the Smart PLS (Partial Lest Square) program 3. Analysis research results, indicators in research that are valid. The work flexibility variable has a significant influence on job satisfaction. The job satisfaction variable is not significant on employee performance. This information can help a company identify employees.